An analysis of age-standardized suicide rates in Muslim-majority countries in 2000-2019 - Bob Lew; David Lester; Kairi Kõlves; Paul S. F. Yip; Ying-Yeh Chen; Won Sun Chen; M. Tasdik Hasan; Harold G. Koenig; Zhi Zhong Wang; Muhamad Nur Fariduddin; Emek Yuce Zeyrek-Rios; Caryn Mei Hsien Chan; et al. (BMC, 2022)
Abstract Background This study examines the 20-year trend of suicide in 46 Muslim-majority countries throughout the world and compares their suicide rates and trends with the global average. Ecological-level associations between the proportion of the Muslim population, the age-standardized suicide rates, male-to-female suicide rate ratio, and the Human Development Index (HDI) in 2019 were examined. Methods Age-standardized suicide rates were extracted from the WHO Global Health Estimates database for the period between 2000 and 2019. The rates in each country were compared with the age-standardized global average during the past 20 years. The countries were further grouped according to their regions/sub-regions to calculate the regional and sub-regional weighted age-standardized suicide rates involving Muslim-majority countries. Correlation analyses were conducted between the proportion of Muslims, age-standardized suicide rate, male: female suicide rate ratio, and the HDI in all countries. Joinpoint regression was used to analyze the age-standardized suicide rates in 2000-2019. Results The 46 countries retained for analysis included an estimated 1.39 billion Muslims from a total worldwide Muslim population of 1.57 billion. Of these countries, eleven (23.9%) had an age-standardized suicide rate above the global average in 2019. In terms of regional/sub-regional suicide rates, Muslim-majority countries in the Sub-Saharan region recorded the highest weighted average age-standardized suicide rate of 10.02/100,000 population, and Southeastern Asia recorded the lowest rate (2.58/100,000 population). There were significant correlations between the Muslim population proportion and male-to-female rate ratios (r=-0.324, p=0.028), HDI index and age-standardized suicide rates (r=-0.506, p<0.001), and HDI index and male-to-female rate ratios (r=0.503, p<0.001) in 2019. Joinpoint analysis revealed that seven Muslim-majority countries (15.2%) recorded an increase in the average annual percentage change regarding age-standardized suicide rates during 2000-2019. Conclusions Most Muslim-majority countries had lower age-standardized suicide rates than the global average, which might reflect religious belief and practice or due to Muslim laws in their judicial and social structure which may lead to underreporting. This finding needs further in-depth country and region-specific study with regard to its implication for public policy.